Development of Occupational Health and Safety Information System in Construction Company Using RAD Method - Denny Jean Cross Sihombing (SEAN Institute, 2023)
This research addresses issues related to Occupational Health and Safety (OHS) in the construction industry, which involves high risks in the working environment. The main problems identified include accident incidents, insufficient training, inadequate use of personal protective equipment, and complex OHS management when involving subcontractors. This research used the Rapid Application Development Method (RAD) to develop an efficient OHS information system. The result of this research includes an OHS information system that is ready to be implemented in the company's construction environment. Implementation involves training for users and staff who will use the system. User evaluation involved field users, system administrators, and project management. Test results showed that 85% of field users found the user interface easy to use, 90% of system administrators found the system easy to manage incident data, and project management gave an upbeat assessment of integrating the OHS system with the existing project management system. The contribution of this research is the development of an efficient OHS information system for construction companies.